Velocidade do som em matéria quente e densa de quarks - Pasqualotto, Arthur Efraim Bressan (2022)
In this work two different approaches to the regularization of thermal integrals in the NJL (Nambu–Jona-Lasinio) SU(2) model are investigated from the phenomenological point of view. Showing the usefullness of the speed of sound in the understanding of the QCD (Quantum chromodynamics) phenomenology at high temperatures, where it can be used as an indicator of the validity of the model, and also at high densities, where it can demonstrate important caracteristics for the EOS (Equation of State) of compact stars. Effects of the chiral chemical potential on the speed of sound and it’s consequences on the quark stars are exposed. We also compare two different methods of regularizarion of the vacuum integrals, TRS (Traditional Regularization Scheme) and MSS (Medium Separation Scheme).